An investigation into the temperature phase transitions of synthesized materials with Al- and Mg-doped lithium manganese oxide spinels by in situ powder X-ray diffraction. Issue 1 (23rd December 2016) - Snyders, C. D.; Ferg, E. E.; Billing, D.
Abstract : Three spinel materials were prepared and characterized by in situ powder X-ray diffraction (PXRD) techniques to track their phase changes that occurred in the typical batch synthesis process from a sol–gel mixture to the final crystalline spinel oxide. The materials were also characterized by thermal gravimetric analysis, whereby the materials decomposition mechanisms that were observed as the precursor, was gradually heated to the final oxide. The results showed that all the materials achieved their total weight loss at about 400 °C. The in situ PXRD analysis showed the progression of the phase transitions where certain of the materials changed from a crystalline precursor to an amorphous intermediate phase and finally to the spinel cathode oxide (Li1.03 Mg0.2 Mn1.77 O4 ). For other materials, the precursor would start as an amorphous phase and upon heating, convert into an impure intermediate phase (Mn2 O3 ) before forming the final spinel oxide (Li1.03 Mn1.97 O4 ). On the other hand, the LiAl0.4 Mn1.6 O4 would start with an amorphous precursor, with no intermediate phases and immediately formed the final spinel oxide phase. The in situ PXRD study also showed the increases in the materials respective lattice parameters of the crystalline unit cells upon heating and the significant increases in their crystallite sizes when heated above 600 °C.